An Analysis of the Historiographic Tradition Surrounding the Extraordinary Chambers in the Cambodian Courts - Baker, Anthony (Journal of Humanities and Social Sciences Studies, 2023)
From 1975 to 1979, The Democratic Kampuchea, or the Khmer Rouge, killed between one and a half to two million people, or twenty percent of the population of Cambodia through starvation, torture, and other means. This period is often cited as prime example of a genocide, yet forty years have passed and only four people have been held accountable for these crimes. In 2003, after years of negotiation with the government of Hun Sen, the prime minster of Cambodia from 1985 until the present, the United Nations and the government of Cambodia decided to establish the Extraordinary Chambers in the Courts of Cambodia for the prosecution of the people many believe responsible for the death of over a million people. Yet, from 2003 until the present, as the courts are still in operation, only four people have been prosecuted despite sixteen years and 300 million dollars from the international community.[1] Despite the Cambodian Genocide being a prime example of genocide, the Extraordinary Chambers in the Courts of Cambodia, or ECCC, has proven to be a complete failure for the millions of dead, and the many millions more who lived through the events, and continue to live with the memory every day. Historians, lawyers, and international scholars have debated the issues surrounding why the ECCC has failed to deliver the promises of justice. Over the course of this paper we will be looking at the historiographic tradition surrounding the Extraordinary Chambers in the Cambodian Courts, dividing the works into two different camps. These two camps differ in their opinion on the fatal flaw with regard to the ECCC. These two camps of thought are, one, that political interference by the authoritarian Hun Sen government has, over the courts ten plus years of existence, used its power to prevent any real progress from being made. The other camp argues that the United Nations 2003 agreement with its international standards of justice does not fit into the national ideal of justice and that hybrid courts that attempt to balance international and national priorities have been flawed since its creation. By providing a detailed analysis of these sources the goal will be to find how the two different camps make their arguments and perhaps how scholars have proposed solutions to the difficulties of the Hun Sen government and the UN to attempt to find justice in Cambodia.